Evaluating consistency of physical activity and exercise prescription in the UK for people with diabetes – a Delphi study - Strongman, Clare; Cavallerio, Francesca; Timmis, Matthew A.; Morrison, Andrew (Frontiers in Clinical Diabetes and Healthcare, 2023)
Introduction Increased physical activity is recommended as a cost-effective measure to tackle long-term management of people with diabetes, but research on interventions lacks consistency in terms of effective duration and modality. Methods The aim of this study was to evaluate expert consensus on exercise and physical activity prescription via a three-round Delphi study conducted with 45 UK-based health and fitness professionals experienced in prescribing exercise or physical activity to people with diabetes. Results The majority of items put forward to the panel reached consensus with 70% or above voting these items as important, but the details of the type, duration and/or modality of exercise or physical activity prescription within these items often contradicted each other, suggesting that patients are receiving inconsistent advice. The range of different exercise prescription found in this study suggests that patients are being given inconsistent and potentially confusing advice, which may affect their participation in exercise and long-term lifestyle change. Conclusion More consistent promotion of advice from healthcare and fitness professionals may help with increasing physical activity in this participant group and achieving long term behavior change, reducing patient symptoms as well as reducing the cost to the National Health Service (NHS).